Setbacks in the process of assimilation of problematic experiences in two cases of emotion-focused therapy for depression. (1st November 2016) - Mendes, Inês; Rosa, Catarina; Stiles, William B.; Caro Gabalda, Isabel; Gomes, Pedro; Basto, Isabel; Salgado, João
Abstract: Objective: Research on the assimilation model has suggested that psychological change takes place in a sequence of stages punctuated by setbacks, that is, by transient reversals in the developmental course. This study analyzed such setbacks in one good outcome case and one poor outcome case of Emotion-focused therapy (EFT) for depression.Method: Intensive analyses of five transcribed sessions from each case identified 26 setbacks in the good outcome case and 27 in the poor outcome case. The reason for each setback was classified into one of four categories: balance strategy, exceeding the therapeutic zone of proximal development either induced by the therapist (ZPD-T) or induced by the client (ZPD-C), or spontaneous switches .Results: In the good outcome case the most frequent reasons for setbacks were balance strategy and spontaneous switches, whereas in the poor outcome case the most frequent reason for setbacks was ZPD-T.Conclusions: As in previously studied therapies, setbacks in EFT, usually represent productive work on relatively less advanced strands of the client's major problems. Results point to the importance of the therapist attending to the limits of the client's therapeutic ZPD.